2012
DOI: 10.1371/198d344bc40a75f927c9bc5024279815
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Veterans Affairs in Emergency Management: A Systematic Literature Review

Abstract: The Department of Veterans Affairs (VA) is a key player in emergency management for both veterans and civilians. Unfortunately, limited evidence-based research findings exist regarding the role and experience of VA during disasters. The present study is a systematic literature review of 41 published, peer-reviewed articles regarding VA and emergency management. Trained researchers utilized a data abstraction tool and conducted a qualitative content analysis. A description of article characteristics include met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…healthcare missions is to provide backup medical resources to both the military health system and to local communities following terrorist incidents and other major disasters [29]. As such, VA has responded to numerous national emergencies [30] and also provided care for non-Veterans during such events [30][31][32][33]. Nevertheless, we found that 57-70% of VA employees would like more training to improve their level of preparedness for a disaster, with the highest proportion of employees reporting the need for training related to epidemics and manmade disasters compared to natural disasters.…”
Section: Discussionmentioning
confidence: 99%
“…healthcare missions is to provide backup medical resources to both the military health system and to local communities following terrorist incidents and other major disasters [29]. As such, VA has responded to numerous national emergencies [30] and also provided care for non-Veterans during such events [30][31][32][33]. Nevertheless, we found that 57-70% of VA employees would like more training to improve their level of preparedness for a disaster, with the highest proportion of employees reporting the need for training related to epidemics and manmade disasters compared to natural disasters.…”
Section: Discussionmentioning
confidence: 99%
“…Veterans include a range of persons with a high level of comorbid health conditions (e.g., higher rates of smoking, substance use disorders and other conditions compared to the general adult population) and other socioeconomic factors (e.g., homelessness) that place them among the more vulnerable members of the population [ 25 ]. Information on flu vaccination uptake comparing Veterans and non-Veterans is limited, especially on a nationally representative sample.…”
Section: Introductionmentioning
confidence: 99%
“…The VHA indeed has an Office of Emergency Management that is responsible for assisting the agency in responding and managing emergencies and natural disaster throughout the four phases of the emergency management cycle: preparedness, response, recovery, and mitigation/prevention. Because of such focus and history related to emergency responses at the VHA (see [15] for a review of the VA's emergency management), it was not surprising that the VHA responded effectively to Katrina. It is important to note that over 1,833 people died in the Hurricane and subsequent floods, where the failures in New Orleans' Hurricane surge protection, considered the worst civil engineering disaster in U.S. history, prompted a lawsuit against the U.S. Army Corps of Engineers.…”
Section: B Vha's Response To Hurricane Katrinamentioning
confidence: 99%
“…The HDR also provides additional benefits, such as providing information to support research and population analyses, facilitating patient access to data and sharing information across the VHA, and improving data quality and data security. Prior research has indeed suggested that one of the cornerstones of the VHA's disaster response was the use of patient tracking [15]. In fact, the patient tracking system in the VHA, the Computerized Patient Record System, was credited with its success in helping the agency provide patient care to thousands of displaced veterans.…”
Section: B Strategy 2 Develop a Universal Data Repositorymentioning
confidence: 99%